Swedish abroad: Motivation to learn, access and use Swedish among university-level learners in Poland - Wandlén Szymczynska,Magda (2025)
The motivation to learn foreign languages is diminishing globally due to the dominance of English in business, media, and education, and additionally to the access it provides to the so-called global community and global identity. Nevertheless, smaller languages such as Swedish continue to be offered at universities worldwide, with students enrolling despite their limited societal use. This study investigates the motivations and linguistic behaviors of Polish university-level learners of Swedish (as a foreign language) with a particular focus on instrumentality, integrativeness, engagement and the influence of English. The analysis draws on the Socio-Educational Model (Gardner, 1985), the L2 Motivational Self-System (Dörnyei & Ushioda, 2009), and the concept of Willingness to Communicate (Macintyre et al., 1998). Findings show that instrumental goals, especially career opportunities, were the primary motivators, while integrative purposes appear to be of minor importance. The learners engaged in a variety of extramural activities, predominantly passive, and had limited active/productive use of Swedish. English emerged as an important resource in formal or high-stakes situations while Swedish was more frequently used in casual contexts, underscoring the role of English as a global communicative tool. The study highlights the interplay of motivation, confidence, and English dominance in shaping Swedish learning abroad, offering insights for future research on languages other than English.
Keywords: Motivation in Foreign Language Acquisition (FLA); Languages Other Than English (LOTE); Psychology of Language; L2 Motivational Self System (L2MSS); Willingness to communicate (WTC); Language exposure